Using an algorithmic approach for grouping roles and sub-units - Nicolay Worren; Tore Christiansen; Kim Verner Soldal (Journal of Organization Design, 2020)
A key task in organization design is to group elements (e.g., roles) into sub-units (e.g., teams or departments). This task is computationally challenging as one must take into consideration a potentially large number of interdependencies between the elements. It also requires data about work processes in the organization, which are rarely present. We have initiated a research program that aims at developing a tool-Reconfig-to improve grouping decisions. It first collects data from employees about their working relationships (i.e., interdependencies) and then uses a computer algorithm to cluster the data in the most optimal manner. The clustered solution represents the formal structure that minimizes coordination costs by grouping the most highly interdependent elements together. We describe the tool, report on two pilot applications, and discuss both the future potential and limitations of the approach.
Keywords: 650; Organization design; Clustering algorithm; Design structure matrix (DSM); Interdependencies; Software tool